Risk of geographic atrophy in the comparison of age-related macular degeneration treatments trials - Grunwald, Juan E; Daniel, Ebenezer; Huang, Jiayan; Ying, Gui-Shuang; Maguire, Maureen G; Toth, Cynthia A; Jaffe, Glenn J; Fine, Stuart L; Blodi, Barbara; Klein, Michael L; Martin, Alison A; Hagstrom, Stephanie A; et al. (Ophthalmology (Rochester, Minn.), 2014)
To describe risk factors for geographic atrophy (GA) in the Comparison of Age-related Macular Degeneration Treatments Trials (CATT). Cohort within a randomized clinical trial. We analyzed 1024 CATT patients with no GA visible on color fundus photographs (CFPs) and/or fluorescein angiograms (FAs) at enrollment. Eyes were assigned to ranibizumab (0.5 mg) or bevacizumab (1.25 mg) treatment and to a 2-year monthly or pro re nata (PRN) injection regimen, or monthly injections for 1 year and PRN for 1 year. Demographic, genetic, and baseline ocular characteristics and lesion features of CFP/FA and optical coherence tomography (OCT) were evaluated as risk factors for GA through 2 years of follow-up. Time-dependent Cox proportional hazard models were used to estimate adjusted hazard ratios (aHRs). Development of GA. By 2 years, GA developed in 187 of 1024 patients (18.3%). Baseline risk factors for GA development included baseline visual acuity (VA) ≤20/200 (aHR, 2.65; 95% confidence interval [CI], 1.43-4.93), retinal angiomatous proliferation (RAP; aHR, 1.69; 95% CI, 1.16-2.47), GA in the fellow eye (aHR, 2.07; 95% CI, 1.40-3.08), and intraretinal fluid at the foveal center (aHR, 2.10; 95% CI, 1.34-3.31). Baseline factors associated with lower risk for GA development included blocked fluorescence (aHR, 0.49; 95% CI, 0.29-0.82), OCT measurements of subretinal fluid thickness of >25 μ (aHR, 0.52; 95% CI, 0.35-0.78), subretinal tissue complex thickness of >275 compared with ≤75 μ (aHR, 0.31; 95% CI, 0.19-0.50), and vitreomacular attachment (aHR, 0.55; 95% CI, 0.31-0.97). Ranibizumab compared with bevacizumab had a higher risk (aHR, 1.43; 95% CI, 1.06-1.93), and monthly dosing had a higher risk (aHR, 1.59; 95% CI, 1.17-2.16) than PRN dosing. There were no strong associations between development of GA and the presence of risk alleles for CFH, ARMS 2, HTRA1, C3, or TLR3. Approximately one fifth of CATT patients developed GA within 2 years of treatment. Independent baseline risk factors included poor VA, RAP, foveal intraretinal fluid, monthly dosing, and treatment with ranibizumab. Anti-vascular endothelial growth factor therapy may have a role in the development of GA.